VALIDASI METODE PENETAPAN KADAR KALIUM ASESULFAM, KAFEIN DAN ASPARTAM DALAM SEDIAAN MINUMAN SERBUK KOPI SACHET SECARA KROMATOGRAFI CAIR KINERJA TINGGI DENGAN DETEKTOR UV - , Mohamad Bagir, Prof. Dr. Sudibyo Martono, M.S., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Coffe powder baverages in sachet contained caffeine, aspartame, and potassium acesulfame were widely spread and consumed by public. but there were no analytical methods to measure caffeine, aspartame and potassium acesulfame in those product using HPLC equiped by UV detector. Aims of this study was to obtain high performance liquid chromatography method that met the validation parameters included selectivity, linearity, accuracy, precision, limit of detection and limit of quantitation, and robustness to determine concentration of those analytes in coffe powder baverages samples. The HPLC system consisted of Waters Atlantis dC18 (lenght 150 mm, internal diameter 3,6 mm, particle size 5 Î¼m) as a stationary phase, the mobile phase is a mixtures of 25 mM phosphat buffer pH 3,5 with 20% of etanol, with a flow rate of 1,0 mL/menit, detected by UV detector, operating time of 10 minutes and 30oC as operating temperature. The method validation showed a good selectivity. Linearity range were 8 - 28 mg/L for potassium acesulfame and aspartame, while 50 - 200 mg/L mg/L for caffeine, with correlation coefficient (r) > 0.995 for all analytes. Recoveries of the analytes from spiked energy drink samples were between 90 - 107% for potassium acesulfame and aspartame and 95 - 105% for caffein. Nevertheles, robustness showed this method had not a good robust.